Implementation of Jakarta’s Joint New Student Admission Policy: A Case Study in Private High Schools - Azzahra, Siti Fatimah; Kurniady, Dedy Achmad; Kurniatun, Taufani Chusnul (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
The Joint New Student Admission System (PPDB Bersama) was introduced by Jakarta's Provincial Education Office to expand equitable access to quality education for economically vulnerable students through government-private school collaboration. Despite its equity goals, implementation faces administrative, technical, and organizational challenges. This qualitative case study analyzes policy implementation at three private senior high schools in West Jakarta using Edward III's framework: communication, resources, disposition, and bureaucratic structure. Data were collected through interviews, focus group discussions, and document analysis involving principals, staff, teachers, and students. Findings reveal that communication remains inconsistent due to fragmented policy dissemination and limited parental understanding; human and technological resources are adequate but constrained by verification procedures and system instability; implementers demonstrate strong commitment to supporting vulnerable students, though the no-transfer policy creates unintended disciplinary issues; and bureaucratic procedures follow official guidelines but are hindered by rigid quotas and limited school-level autonomy. The study concludes that while PPDB Bersama enhances educational equity, its effectiveness requires strengthened socialization, improved cross-agency coordination, flexible resource allocation, and adaptive bureaucratic mechanisms. Strategic recommendations are proposed to optimize policy performance and reinforce private schools' role in achieving equitable and inclusive education in Jakarta.